PRINSIP KESANTUNAN BERDASARKAN MAKSIM LEECH DALAM KUMPULAN NASKAH DRAMA GENG TOILET KARYA SOSIAWAN LEAK DAN RELEVANSINYA SEBAGAI BAHAN AJAR TEKS DRAMA DI SEKOLAH MENENGAH ATAS - Vinsca Sabrina Claudia; Ani Rakhmawati; Budi Waluyo (Universitas Sebelas Maret, 2018)
The research aims to explain and describe (1) speech acts in the dialogue collection of drama text Geng Toilet; (2) the principle of politeness in the dialogue collection of drama text Geng Toilet; (3) the relevance collection of drama text Geng Toilet as a teaching material for drama text in High School. The method use in this research is descriptive qualitative. The result of the research indicates the result of the research indicates the speech act in the collection of the drama text Geng Toilet based on speech that contains action include locution,illocution, and perlocution. While, speech acts based on the sentence mode include direct speech acts and indirect speech acts.Next, the principle of politeness in the dialogue collection of drama text Geng Toilet includes maxim of agreement or consent, maxim of generosity, maxim acceptance or praise or appreciation, maxim of humility or simplicity, and maxim of sympathy. the collection of drama text Geng Toilet can be used as a teaching materials for drama text in High School.